The Talasim And its Effecton Agriculture in The Meddle Meghreb Central During The Inter Mediate Age. - laredj, daoudi (Journal of Social Sciences and Humanities, 2021)
Research in This topicis an important issue related to farming, and we try A comprehensive picture of Agriculture, The longer the paint is a phenomenon spread in society the argument had an effect on the peasants. Given the inability of the science of Agriculture for a solution to all the problems of Agriculture. The adoption by farmers of its effectiveness in eliminating pests ؛ Based on that it was our interest to study the effect of paint on the cultivator.